Pemetaan Tingkat Korosifitas Atmosfer di Wilayah Kota Surabaya dengan Indikator Baja Galvalum - rohmannudin, tubagus noor; Ragha Radithya Noer Putra; Sulistijono (Universitas Nusa Putra, 2025)
This study maps the levels of atmospheric corrosion in five regions of Surabaya. The metal used is 55% Al-Zn galvalume steel frame with three types: hollow. The exposure period was 150 days, and the corrosion rate was calculated using the weight loss method. XRD testing, metallography, and visual inspections were also conducted to compare the results across the five regions. The study concludes that a high level of atmospheric corrosivity for 55% Al-Zn galvalume steel of the hollow-type 55% Al-Zn galvalume steel, high atmospheric corrosivity was observed in Rungkut (1.07 x 10⁻¹ mpy), Bulak (8.70 x 10⁻² mpy), Asemrowo (7.94 x 10⁻² mpy), Kenjeran (6.76 x 10⁻² mpy), and Pabean Cantikan (6.16 x 10⁻² mpy). Moderate levels were found in Jambangan (5.92 x 10⁻² mpy), Sukolilo (5.75 x 10⁻² mpy), Pakal (5.46 x 10⁻² mpy), Wonokromo (5.38 x 10⁻² mpy), and Tandes (5.30 x 10⁻² mpy). Low levels were observed in Gubeng (5.28 x 10⁻² mpy), Wiyung (4.87 x 10⁻² mpy), Simokerto (4.69 x 10⁻² mpy), Bubutan (4.28 x 10⁻² mpy), and Tegalsari (3.69 x 10⁻² mpy). The mapping was carried out based on the corrosion rate in each sub-district within the exposure area. These corrosion rates were influenced by the presence of industrial activity in the respective sub-districts, as well as their geographic location.